Influence of foulant particle shape on membrane fouling in dead-end microfiltration - Lay, Huang Teik (2022)
In view of the proliferating applications involving membrane-based separation, the inevitable membrane fouling phenomenon is well-studied. However, the influence of foulant shape on membrane fouling remained incompletely understood. Therefore, the goal of this study was to investigate the fouling behaviors by three different shapes of latex particles (namely, peanut, pear and sphere) with similar mean diameters in the range of 3.5–3.8 μm. External and internal fouling were studied using polycarbonate track-etched (PCTE) membranes with nominal pore sizes of 2 and 8 μm, respectively. Flux data were taken, and fouling models, optical coherence tomography (OCT) and field-emission scanning electron microscope were employed. Regarding external membrane fouling, the sphere-shaped particles displayed the worst flux decline, which is tied to the greatest tendency to deposit on the membrane pores, as revealed by the network fouling model. As for internal fouling, the flux decline curves were more similar among the particle types. The fouling model shows the sphere-shaped particles gave the densest internal cake, which caused slightly steeper flux decline in the latter part of the filtration. Furthermore, OCT indicates that the highest fouling fractions at 7.5 μm below the membrane were exhibited for the peanut-shaped particles, which is due to the preferential vertical orientation resulting in deeper penetration. Results here highlight the non-negligible influence of foulant particle shape, which warrants further understanding and accounting for membrane fouling studies.